Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Homodyne detection with on-off detector systems - Lipfert, T.; Sperling, Jan; Vogel, W. (Physical Review A)

Continuous sampling of the squeezed-state nonclassicality - Agudelo, E.; Sperling, Jan; Vogel, W.; Köhnke, S.; Mraz, M.; Hage, B. (Physical Review A)

Unified nonclassicality criteria - Ryl, S.; Sperling, Jan; Agudelo, E.; Mraz, M.; Köhnke, S.; Hage, B.; Vogel, W. (Physical Review A)

Entanglement and phase properties of noisy NOON states - Bohmann, M.; Sperling, Jan; Vogel, W. (Physical Review A)

Entanglement witnesses for indistinguishable particles - Reusch, A.; Sperling, Jan; Vogel, W. (Physical Review A)

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Projective filtering of the fundamental eigenmode from spatially multimode radiation - Pérez, A. M.; Sharapova, Polina; Straupe, S. S.; Miatto, F. M.; Tikhonova, O. V.; Leuchs, G.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Schmidt modes in the angular spectrum of bright squeezed vacuum - Sharapova, Polina; Pérez, A. M.; Tikhonova, O. V.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, Michael; Jachura, M.; Brecht, Benjamin; Avenhaus, M.; Silberhorn, Christine (Physical Review A)

Detection of nonlocal superpositions - Gutiérrez-Esparza, A. J.; Pimenta, W. M.; Marques, B.; Matoso, A. A.; Sperling, Jan; Vogel, W.; Pádua, S. (Physical Review A)

Witnessing the degree of nonclassicality of light - Mraz, M.; Sperling, Jan; Vogel, W.; Hage, B. (Physical Review A)

Unified quantification of nonclassicality and entanglement - Vogel, W.; Sperling, Jan (Physical Review A)

Quantum state engineering by click counting - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Bipartite bound entanglement in continuous variables through degaussification - Steinhoff, F. E. S.; de Oliveira, M. C.; Sperling, Jan; Vogel, W. (Physical Review A)

Operational Gaussian Schmidt-number witnesses - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review A)

Demonstration of coherent time-frequency Schmidt mode selection using dispersion-engineered frequency conversion - Brecht, Benjamin; Eckstein, Andreas; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sansoni, Linda; Silberhorn, Christine (Physical Review A)

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, M. S.; Jachura, M.; Brecht, B.; Avenhaus, M.; Silberhorn, C. (Physical Review A)

Time-multiplexed measurements of nonclassical light at telecom wavelengths - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Efficient algorithm for optimizing data-pattern tomography - Motka, L.; Stoklasa, B.; Rehacek, J.; Hradil, Z.; Karasek, V.; Mogilevtsev, D.; Harder, G.; Silberhorn, Christine; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.

Regeneration of Airy pulses in fiber-optic links with dispersion management of the two leading dispersion terms of opposite signs - Driben, R.; Meier, Torsten (Physical Review A)
Dispersion management of periodically alternating fiber sections with opposite signs of two leading dispersion terms is applied for the regeneration of self-accelerating truncated Airy pulses. It is demonstrated that for such a dispersion management scheme, the direction of the acceleration of the pulse is reversed twice within each period. In this scheme the system features light hot spots in the center of each fiber section, where the energy of the light pulse is tightly focused in a short temporal slot. Comprehensive numerical studies demonstrate a long-lasting propagation also under the influence of a strong fiber Kerr nonlinearity.

Correlation measurements with on-off detectors - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Multipartite entangled light from driven microcavities - Pagel, D.; Fehske, H.; Sperling, Jan; Vogel, W. (Physical Review A)

Quasiprobabilities for multipartite quantum correlations of light - Agudelo, E.; Sperling, Jan; Vogel, W. (Physical Review A)

Characterizing entanglement in pulsed parametric down-conversion using chronocyclic Wigner functions - Brecht, Benjamin; Silberhorn, Christine (Physical Review A)

Interference-induced asymmetric transmission through a monolayer of anisotropic chiral metamolecules - Zhang, Shuang; Liu, Fu; Zentgraf, Thomas; Li, Jensen (Physical Review A)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Time-correspondence differential ghost imaging - Li, Ming-Fei; Zhang, Yu-Ran; Luo, Kai Hong; Wu, Ling-An; Fan, Heng (Physical Review A)

Quantification of nonclassicality - Gehrke, C.; Sperling, Jan; Vogel, W. (Physical Review A)

Strongly entangled light from planar microcavities - Pagel, D.; Fehske, H.; Sperling, Jan; Vogel, W. (Physical Review A)

Analytical progress on symmetric geometric discord: Measurement-based upper bounds - Miranowicz, Adam; Horodecki, Paweł; Chhajlany, Ravindra W.; Tuziemski, Jan; Sperling, Jan (Physical Review A)

True photocounting statistics of multiple on-off detectors - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Multiphoton state engineering by heralded interference between single photons and coherent states - Bartley, Tim; Donati, Gaia; Spring, Justin B.; Jin, Xian-Min; Barbieri, Marco; Datta, Animesh; Smith, Brian J.; Walmsley, Ian A. (Physical Review A)

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Determination of the Schmidt number - Sperling, Jan; Vogel, W. (Physical Review A)

High-performance single-photon generation with commercial-grade optical fiber - Söller, Christoph; Cohen, Offir; Smith, Brian J.; Walmsley, Ian A.; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Bridging visible and telecom wavelengths with a single-mode broadband photon pair source - Söller, C.; Brecht, Benjamin; Mosley, P. J.; Zang, L. Y.; Podlipensky, A.; Joly, N. Y.; Russell, P. St. J.; Silberhorn, Christine (Physical Review A)

Nonlocal Talbot self-imaging with incoherent light - Luo, Kai Hong; Chen, Xi-Hao; Liu, Qian; Wu, Ling-An (Physical Review A)

Verifying continuous-variable entanglement in finite spaces - Sperling, Jan; Vogel, W. (Physical Review A)

Representation of entanglement by negative quasiprobabilities - Sperling, Jan; Vogel, W. (Physical Review A)

Necessary and sufficient conditions for bipartite entanglement - Sperling, Jan; Vogel, W. (Physical Review A)

Indirect spin dephasing via charge-state decoherence in optical control schemes in quantum dots - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review A)
We demonstrate that an optically driven spin of a carrier in a quantum dot undergoes indirect dephasing via conditional optically induced charge evolution even in the absence of any direct interaction between the spin and its environment. A generic model for the indirect dephasing with a three-component system with spin, charge, and reservoir is proposed. This indirect decoherence channel is studied for the optical spin manipulation in a quantum dot with a microscopic description of the charge-phonon interaction taking into account its non-Markovian nature.
Keywords: tet_topic_qd

Role of multiphoton bunching in high-order ghost imaging with thermal light sources - Liu, Qian; Chen, Xi-Hao; Luo, Kai Hong; Wu, Wei; Wu, Ling-An (Physical Review A)

Second-order Talbot effect with entangled photon pairs - Luo, Kai Hong; Wen, Jianming; Chen, Xi-Hao; Liu, Qian; Xiao, Min; Wu, Ling-An (Physical Review A)

Signatures of nonclassicality in mixed-state quantum computation - Datta, Animesh; Gharibian, Sevag (Physical Review A)
We investigate signatures of non-classicality in quantum states, in particular, those involved in the DQC1 model of mixed-state quantum computation [Phys. Rev. Lett. 81, 5672 (1998)]. To do so, we consider two known non-classicality criteria. The first quantifies disturbance of a quantum state under locally noneffective unitary operations (LNU), which are local unitaries acting invariantly on a subsystem. The second quantifies measurement induced disturbance (MID) in the eigenbasis of the reduced density matrices. We study the role of both figures of non-classicality in the exponential speedup of the DQC1 model and compare them vis-a-vis the interpretation provided in terms of quantum discord. In particular, we prove that a non-zero quantum discord implies a non-zero shift under LNUs. We also use the MID measure to study the locking of classical correlations [Phys. Rev. Lett. 92, 067902 (2004)] using two mutually unbiased bases (MUB). We find the MID measure to exactly correspond to the number of locked bits of correlation. For three or more MUBs, it predicts the possibility of superior locking effects.

Electric-field effects on nematic droplets with negative dielectric anisotropy - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Dynamics of blue-phase selective reflections in an electric field - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Kwok, S. L.; Xu, J.; Heppke, G. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics